2019
DOI: 10.11604/pamj.2019.32.84.14742
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, beliefs and practices regarding sickle cell eye disease of patients at the sickle cell unit, Jamaica

Abstract: Introduction Sickle cell disease can result in visually threatening eye disease (proliferative sickle cell retinopathy). This can be prevented with timely eye screening. It is important for patients to understand their role. Our research is to determine the knowledge, beliefs and practices (KBP) regarding eye disease of Sickle Cell patients and the impact of genotype, demographic and socio-economic status. Methods Cross-sectional study at the Sickle Cell Unit, Jamaica d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Secondary and higher levels of education were the most represented, with rates of 46.40% and 44.40% respectively. The predominance of patients with secondary education was also found in the study carried out by Mowatt et al where 61% of patients attended secondary education, while 25% attended higher education [15].…”
Section: Socio-demographicsupporting
confidence: 68%
“…Secondary and higher levels of education were the most represented, with rates of 46.40% and 44.40% respectively. The predominance of patients with secondary education was also found in the study carried out by Mowatt et al where 61% of patients attended secondary education, while 25% attended higher education [15].…”
Section: Socio-demographicsupporting
confidence: 68%
“…Mowatt et al also administered a questionnaire to patients with SCD; only 28% of subjects answered “Yes” to the question “Do you see your eye doctor for regular checkups?”. Only 42% of respondents answered that they had seen an ophthalmologist once a year, and 21% reported never having seen an ophthalmologist [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores were correlated to more regular ophthalmological follow-ups. In addition, the authors found that employment was significantly associated with regular eye examinations in SCD patients, suggesting financial stability may be related to patient compliance with proper ophthalmic care [ 16 ]. A survey by Alsheri et al found that the majority (57.3%) of their SCD patients were not aware of the ocular complications of SCD [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…23% of the population in the pediatric ward had homozygous HbSS and 43.5% have sickle cell gene. The finding from a cohort study in Kenya also revealed that 69.3% of children admitted sickle cell patients were undiagnosed (Lizette, Ayodeji, & Jennifer, 2019).…”
Section: Awareness and Epidemiology Of Sickle Cell Diseasementioning
confidence: 93%